Spatially resolved radio signatures of electron beams in a coronal shock - Zhang, Peijin (EDP Sciences, 2025)
Context. Type II radio bursts are a type of solar radio bursts associated with coronal shocks. Type II bursts usually exhibit fine structures in dynamic spectra that represent signatures of accelerated electron beams. So far, the sources of individual fine structures in type II bursts have not been spatially resolved in high-resolution low-frequency radio imaging.
Aims. The objective of this study is to resolve the radio sources of the herringbone bursts found in type II solar radio bursts and investigate the properties of the acceleration regions in coronal shocks.
Methods. We used low-frequency interferometric imaging observations from the Low Frequency Array to provide a spatially resolved analysis for three herringbone groups (A, B, and C) in a type II radio burst that occurred on 16 October 2015.
Results. The herringbones in groups A and C have a typical frequency drift direction and a propagation direction along the frequency. Their frequency drift rates correspond to those of type III bursts and previously studied herringbones. Group B has a more complex spatial distribution, with two distinct sources separated by 50 arcsec and no clear spatial propagation with frequency. One of the herringbones in group B was found to have an exceptionally large frequency drift rate.
Conclusions. The characteristics derived from imaging spectroscopy suggest that the studied herringbones originate from different processes. Herringbone groups A and C most likely originate from single-direction beam electrons, while group B may be explained by counterstreaming beam electrons.